MICROBIAL HAZARDS ASSOCIATED WITH FISH FROM DIFFERENT WATER BODIES IN RELATION TO PATHOGENS OF PUBLIC HEALTH SIGNIFICANCE - MISHRA, S. S.; DHIMAN, M.; DAS, PRIYANKA; DUTTA, C.; MALI, P.; SAMANTA, S. (Journal of the Inland Fisheries Society of India, 2022)
Fish and water samples from a sewage-fed bhery, Mathura beel and the Hooghly river were examined for total platecount, total Vibrio, fecal coliforms, E.coli, Aeromonas, Salmonella, faecal Streptococci. Results revealed presence of most of these pathogens in water samples but comparatively low level of pathogens in fish muscle. Fish and water collected from Hooghly river were found to be more polluted as indicated by higher microbial load, fecal coli and Vibrio counts, followed by that collected from sewage-fed bhery and Mathura beel. Microbial isolates were screened using PCR for specific detection of E.coli, enterotoxigenic E.coli (ETEC), Vibrio cholerae, Salmonella spp. and Aeromonas hydrophilla. Most fish samples were found negative for ETEC and V. cholera but few were positive for E.coli, Aeromonas and Salmonella. However, most water and gill samples were found positive for E.coli and Aeromonas. Antibiotic susceptibility test of E.coli, Salmonella, Aeromonas and Vibrio isolates indicated higher resistance to multiple antibiotics.Key words : Microbial hazards, Sewage-fed bhery, PCR, antibiotic sensitivity